Nuezhenide of the fruits of Nuzhenzi (Ligustrum lucidum Ait.) is a functional analog of ghrelin - Wang, Chia-Hao; Tseng, Ching-Yu; Hsu, Wei-Li; Tzen, Jason T.C. (Journal of ethnopharmacology, 2025)
The dried fruit of Ligustrum lucidum Ait. (FLL), known as Nuzhenzi, is traditionally recognized for its anti-aging properties in Chinese medicine. Nuezhenide, a water-soluble secoiridoid present in FLL, has demonstrated various pharmacological activities including neuroprotection, enhancement of learning and memory, antiosteoporotic, and antiviral activities. These therapeutic benefits align with the anti-aging effects attributed to ghrelin, particularly in the modulation of growth hormone secretagogue receptor type 1a (GHSR-1a) signaling. This study aimed to investigate the potential of FLL extracts, particularly its major compound nuezhenide, as agonists of GHSR-1a, a receptor implicated in anti-aging mechanisms, utilizing a stable GHSR-1a-expressing cell line. HEK293T cells expressing GHSR-1a-mCherry were used to assess the effects of FLL extract and its major compound, nuezhenide, on cell viability and ERK1/2 signaling. Molecular docking simulations predicted the interaction between nuezhenide and the GHSR-1a binding pocket. The impact of nuezhenide on ERK1/2 phosphorylation was evaluated, along with the involvement of phospholipase C and calcium signaling in this process. Molecular docking simulations indicated that nuezhenide could interact with the GHSR-1a receptor, similar to teaghrelin, another known ghrelin analog. Experimental data showed that FLL extracts and nuezhenide enhanced cell viability and ERK1/2 activation in GHSR1a-mCherry HEK293T cells. The effect was specifically mediated by GHSR-1a, as confirmed by SP-analog treatment. Further analysis revealed that nuezhenide-induced ERK1/2 activation is likely mediated through a phospholipase C-dependent pathway involving intracellular calcium release. This study demonstrated for the first time that nuezhenide acts as a putative GHSR-1a agonist, promoting cell proliferation and activating ERK1/2 signaling via phospholipase C and calcium pathways. These findings support the traditional use of FLL as an anti-aging herbal remedy and suggest that nuezhenide could be developed as a therapeutic agent targeting GHSR-1a-mediated pathways. [Display omitted]